Fish out of water: consumers’ unfamiliarity with the appearance of commercial fish species - Marine Cusa; Luara Falcão; Joseph De Jesus; Cristina Biolatti; Lancelot Blondeel; Fiona S. A. Bracken; Lisa Devriese; Sandra Garcés-Pastor; Styliani Minoudi; Chrysoula Gubili; Pier Luigi Acutis; Stefano Mariani (Sustainability Science, 2021)
Seafood labels play an increasingly key role in assisting consumers in purchasing processed and featureless fish products, and in encouraging sustainable fishing and aquaculture practices. While informed purchasing choices are typically influenced by traceability and labelling awareness, they also depend on the consumers’ ability to identify and discriminate the fish species available on the market, which to date remains notably unexplored. We asked 720 people across six European countries to identify pictures of six fish species commonly sold in Europe. We reveal that European consumers have a poor understanding of the appearance of the fish they consume (overall ∼ 30% correct identification), with British consumers performing the poorest and Spanish ones doing best. We noted cultural association with some species, whereby the most regionally consumed fish are more easily recognized. We argue that despite recent improvements in technological solutions, stakeholder dialogue, and policy implementation, seafood market transparency will remain open to malpractice until consumers restore connection with their food.